THE NEED TO PROTECT YOUTH FROM DESTRUCTIVE IDEAS IN THE PROCESS OF GLOBALIZATION (Global Conference on Multidisciplinary Research and Innovation, 2026)
In the context of globalization, the rapid flow of information and the intensification of cultural interaction have created both new opportunities and serious challenges for young people. Along with positive influences, globalization also facilitates the spread of destructive and extremist ideas that can negatively affect the worldview, moral values, and social behavior of youth. This article analyzes the ideological risks faced by young people in the globalized world and emphasizes the importance of strengthening cultural identity, critical thinking, and spiritual–moral education. Particular attention is paid to the role of family, educational institutions, and society in protecting youth from harmful ideologies and in forming ideological immunity.
Keywords: Globalization, youth, destructive ideas, ideological immunity, cultural identity, education, spirituality, social stability.